Zn(ii)2, 9-dimethyl-1, 10-phenanthroline stimulates cultured bovine aortic endothelial cell proliferation. Issue 69 (20th November 2020) - Nakamura, Takehiro; Yoshida, Eiko; Hara, Takato; Fujie, Tomoya; Yamamoto, Chika; Fujiwara, Yasuyuki; Ogata, Fumihiko; Kawasaki, Naohito; Takita, Ryo; Uchiyama, Masanobu; Kaji, Toshiyuki
Abstract : Stimulation of vascular endothelial cell proliferation by Zn-12 can be mediated by the ERK1/2 activation independently of the FGF-2-FGFR pathway. Additionally, there may be other pathways involved in the Zn-12 stimulation. Abstract : Vascular endothelial cells cover the luminal surface of blood vessels in a monolayer. Proliferation of these cells is crucial for the repair of damaged endothelial monolayers. In the present study, we identified a zinc complex, Zn(ii )2, 9-dimethyl-1, 10-phenanthroline (Zn-12), that stimulates the proliferation of bovine aortic endothelial cells in a culture system. No such stimulatory activity was observed for the ligand alone or in combination with other metals; however, the ligand combined with iron weakly stimulated the proliferation, as evidenced by the [ 3 H]thymidine incorporation assay. Inorganic zinc weakly but significantly stimulated proliferation, and intracellular accumulation of zinc was similar between inorganic zinc and Zn-12 treatment, suggesting that the mechanisms by which Zn-12 stimulates vascular endothelial cell proliferation contain processes that differ from those by which inorganic zinc stimulates proliferation. Although expression of endogenous fibroblast growth factor-2 (FGF-2) and its receptor FGFR-1 was unchanged by Zn-12, both siRNA-mediated knockdown of FGF-2 and FGFR inhibition partly but significantly suppressed the stimulation of vascular endothelial cell proliferation by Zn-12, indicating that the zinc complex activates the FGF-2 pathway to stimulate proliferation. Phosphorylation of ERK1/2 and MAPKs was induced by Zn-12, and PD98059, a MEK1 inhibitor, significantly suppressed the stimulatory effect of Zn-12 on vascular endothelial cell proliferation. Therefore, it is suggested that Zn-12 activates the FGF-2 pathway via activation of ERK1/2 signaling to stimulate vascular endothelial cell proliferation, although FGF-2-independent mechanisms are also involved in the stimulation. Zn-12 and related compounds may be promising molecular probes to analyze biological systems of vascular endothelial cells.